A refined photo‐switchable cyclic peptide scaffold for use in β‐turn activation. Issue 5 (18th March 2022) - Johnson, Corey; Harwood, John S.; Lipton, Mark; Chmielewski, Jean
Abstract: The ability to reversibly modulate peptide secondary structures, such as the β‐turn, allows for precise control of biological function, including protein interactions. Herein, we describe the design of two scaffolds containing an azobenzene moiety with flanking alanine or β‐alanine residues to probe essential features for photo‐control of a β‐turn within a cyclic peptide. To efficiently cyclize the designed linear peptides, prior isomerization of the azobenzene‐containing amino acid from the trans to the cis form was necessary. The two cyclic peptides (TAp and TApβ) were found to undergo rapid photochemical conversion to the cis isomer of the azobenzene, with a more gradual thermal reversion to the trans isomer over the course of a week at 37 °C. Spectroscopic analysis and restrained molecular dynamics simulation of the cis form of TAp and TApβ revealed type II and type II' β‐turns within the cyclic peptides, respectively. The trans isomer of the TAp cyclic peptide was found to have a kink within the peptide structure, whereas the longer trans‐TApβ contained a more extended conformation. TApβ, therefore, demonstrates a clearer difference in the cyclic peptide conformations when in the cis versus trans form, a feature that may prove beneficial for use with biologically active β‐turn sequences. Abstract :